2007
DOI: 10.1111/j.1399-3046.2007.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk adenovirus‐infected pediatric allogeneic hematopoietic progenitor cell transplant recipients and preemptive cidofovir therapy

Abstract: ADV has emerged as an important pathogen in children undergoing allogeneic HPCT. A prospective study of the epidemiology of ADV infection and preemptive therapy of high risk ADV infections in children undergoing HPCT was undertaken. Cultures of throat, urine, and stool for viral pathogens and plasma for ADV PCR were obtained prior to transplantation, weekly for the first 100 days, and then monthly for one yr. Children developing high-risk ADV infections were treated preemptively with cidofovir 1 mg/kg/day give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 36 publications
3
78
1
2
Order By: Relevance
“…However, renal dysfunction was transient in the majority of patients with serum creatinine returning to baseline after cessation of CDV therapy. While some studies have reported no toxicities related to the use of CDV 14, 16, 17, 19, 25 , the transient nature of nephrotoxicity observed has been reported by other studies 20, 24 . We were unable to detect any increased risk of nephrotoxicity associated with concomitant administration of additional nephrotoxic agents but this may reflect our small number of study participants.…”
Section: Discussionmentioning
confidence: 72%
“…However, renal dysfunction was transient in the majority of patients with serum creatinine returning to baseline after cessation of CDV therapy. While some studies have reported no toxicities related to the use of CDV 14, 16, 17, 19, 25 , the transient nature of nephrotoxicity observed has been reported by other studies 20, 24 . We were unable to detect any increased risk of nephrotoxicity associated with concomitant administration of additional nephrotoxic agents but this may reflect our small number of study participants.…”
Section: Discussionmentioning
confidence: 72%
“…41 In view of the considerable nephrotoxicity of cidofovir and the high cost of treatment, preemptive therapy for all patients with AdV-positive stool samples is not generally recommended. 1,2,4,21,31,33,42 Prospective quantitative PCR screening in stool specimens and PB in this study of 153 pediatric allogeneic SCTs revealed that virtually all patients with AdV viremia showed rising virus copy numbers in serial stool specimens exceeding the threshold of 10E6 viral particles per gram before first appearance of the virus in PB (Po0.0001). The only exception in this series was a patient with onset of viremia very early after transplant (day þ 11) in whom detection of AdV in PB coincided with first observation of the virus in stool specimens.…”
Section: Discussionmentioning
confidence: 99%
“…En pacientes sometidos a trasplante de hígado, una serie de 484 niños reportó una incidencia de infección de 10% 3 . En pacientes sometidos a trasplante de pulmón, se ha asociado neumonía por ADV con pérdida de injerto, muerte y progresión a bronquiolitis 5 ; en cualquier caso, se ha reportado 6,5 a 58% de viremia asintomática y esta situación no se ha asociado a enfermedad progresiva 16 .…”
Section: Epidemiologíaunclassified